Intralingual Translation: An Attempt at Description - Zethsen, Karen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractIn theory, translation studies does not exclude intralingual translation, but de facto empirical studies or discussions on the subject of intralingual translation are few and far between. This article argues for the proper inclusion of intralingual translation on the grounds of its many similarities with interlingual translation. For the sake of comparison, a general description of intralingual translation and its characteristics on the basis of five different Danish versions of a section of the Bible and an analysis of the microstrategies employed in each version are proposed. Similarities as well as differences between rewording and translation proper are discussed, the conclusion being that the differences between intralingual and interlingual translation seem to be more a question of degree than of kind.